Strategi pemasaran bisnis UMKM pada masa pandemi covid-19 (studi kasus: ruby florist manokwari) - Luckhy N.A Lotte; Makarius Bajari; Ismi Hariyati (Jurnal Pengetahuan dan Pendidikan, 2026)
This study aims to determine the obstacles faced, the marketing strategies used, and the products that Ruby Florist has successfully developed to maintain her business amid the covid-19 pandemic.This type of research uses a qualitative approach to the type of descriptive problem. The object of this research is the marketing strategy for the UMKM business during the covid-19 pandemic carried out by Ruby Florist. Data collection techniques were carried out by participatory observation, interviews, and documentation.The results showed that Ruby Florist implemented 8 marketing strategies to maintain her business amid the covid-19 pandemic, namely digital marketing, product innovation, promo & discount prices, give awat, direct marketing, and word of mouth (WOM).